1998
DOI: 10.1046/j.1365-2672.1998.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities of printing paper machines

Abstract: The microbial content of printing paper machines, running at a temperature of 45-50 degrees C and at pH 4.5-5, was studied. Bacteria were prevalent colonizers of the machine wet end and the raw materials. A total of 390 strains of aerobic bacteria were isolated and 86% of these were identified to genus and species by biochemical, chemotaxonomic and phylogenetic methods. The most common bacteria found at the machine wet end were Bacillus coagulans and other Bacillus species, Burkholderia cepacia, Ralstonia pick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 26 publications
(45 reference statements)
4
112
1
Order By: Relevance
“…Almost all (16/18) of the isolates were members of the family Enterobacteriaceae with Enterobacter and Klebsiella (Raoultella) as the most frequently represented genera. Enterobacter, Klebsiella and Citrobacter species are common in soil, healthy and decaying wood and in plants and also appear to be normal inhabitants in many paper machines [2,24,25,33,47]. According to a Canadian study, these bacteria grew continuously in many of the mills studied with the most likely growth areas being paper machines, biofilms on machinery and piping and the primary clarifier [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all (16/18) of the isolates were members of the family Enterobacteriaceae with Enterobacter and Klebsiella (Raoultella) as the most frequently represented genera. Enterobacter, Klebsiella and Citrobacter species are common in soil, healthy and decaying wood and in plants and also appear to be normal inhabitants in many paper machines [2,24,25,33,47]. According to a Canadian study, these bacteria grew continuously in many of the mills studied with the most likely growth areas being paper machines, biofilms on machinery and piping and the primary clarifier [15].…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharide-producing enterobacteria were found especially in the Finnish mill B and in the Spanish mill, slimy bacteria belonging to, e.g. genera Acinetobacter, Aureobacterium, Bacillus, Brevundimonas, Deinococcus, Methylobacterium, Paenibacillus and Pseudomonas have previously been identified from various other mills [24,34,47].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the slime-forming bacteria (SFB) of pulp, paper and board mills showed that the primary slime producers worldwide were members of Enterobacteriaceae with Enterobacter cloacae, Enterobacter aerogenes, Pantoea agglomerans, Klebsiella pneumoniae and Raoultella spp., as the most frequently species isolated (Sanborn, 1944;Neilson & Sparell, 1976;Väisänen et al, 1998;Blanco, 2003;Gauthier et al, 2000;Gauhier & Archibald, 2001;Beuchamp et al, 2006;Rättö et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, 454 pyrosequencing revealed a much more diverse bacterial community than clone library. Bacteria, mostly Firmicutes and Proteobacteria, are introduced to the paper mill through contaminated cellulosic raw material, fresh incoming water and paper-making chemicals [2] [5]. Physical conditions in the paper mill range from basic to acidic pH, ambient and high temperatures, aerobic and anaerobic environments, etc.…”
Section: Comparison Of the Bacterial Communities Obtained Using 454 Pmentioning
confidence: 99%
“…Culturable bacterial population diversity has been studied in the fiber slurry [5]- [7], white water [5] [8], biofilms [6] [9] [10], and the final recycled products [11] by 16S rRNA gene sequences. In addition, biofilms were also studied by microscopy [5] [9] [10] [12], physiological and biochemical characterization [9] [10] [12], and fatty acids analysis [10] [12]. Unculturable bacterial population diversity has been determined in the fiber slurry [13] [14], white water [14] and biofilms [13]- [15] by 16S rRNA gene sequences.…”
Section: Introductionmentioning
confidence: 99%